Self-control tames the coupling of reactive radicals - Lloyd-Jones, Guy C.; Ball, Liam T. (American Association for the Advancement of Science, 2014)
Highly reactive or unstable chemical reagents are challenging to prepare, store, and safely handle, so chemists frequently generate them in situ from convenient precursors. In an ideal case, the rate of release of the reagent would be matched to the rate of its “capture” in the desired chemical reaction, thereby preventing the reagent from accumulating and minimizing any opportunity for decomposition. However, this synchronization is rarely achieved or even attempted: The rate of release is usually dictated by the conditions of the reaction (1), rather than being regulated by capture of the reagent. In this issue, Tellis et al. (2) on page 433 and Zuo et al. (3) on page 437 independently report the use of iridium photocatalysis (4, 5) to supply highly reactive radical coupling partners (R⋅) to a nickel-catalyzed carbon-carbon bond-forming process (see the figure). Intriguingly, the two points of contact between the iridium and nickel cycles enforce autoregulated release of the radical, ensuring its efficient capture by nickel rather than its decomposition via other pathways.